Concentration‐dependent activation of dopamine receptors differentially modulates GABA release onto orexin neurons. (26th June 2015) - Linehan, Victoria; Trask, Robert B.; Briggs, Chantalle; Rowe, Todd M.; Hirasawa, Michiru
Abstract Dopamine (DA) and orexin neurons play important roles in reward and food intake. There are anatomical and functional connections between these two cell groups: orexin peptides stimulate DA neurons in the ventral tegmental area and DA inhibits orexin neurons in the hypothalamus. However, the cellular mechanisms underlying the action of DA on orexin neurons remain incompletely understood. Therefore, the effect of DA on inhibitory transmission to orexin neurons was investigated in rat brain slices using the whole‐cell patch‐clamp technique. We found that DA modulated the frequency of spontaneous and miniature IPSCs (mIPSCs) in a concentration‐dependent bidirectional manner. Low (1 μm) and high (100 μm) concentrations of DA decreased and increased IPSC frequency, respectively. These effects did not accompany a change in mIPSC amplitude and persisted in the presence of G‐protein signaling inhibitor GDPβS in the pipette, suggesting that DA acts presynaptically. The decrease in mIPSC frequency was mediated by D2 receptors whereas the increase required co‐activation of D1 and D2 receptors and subsequent activation of phospholipase C. In summary, our results suggest that DA has complex effects on GABAergic transmission to orexin neurons, involving cooperation of multiple receptor subtypes. The direction of dopaminergic influence on orexin neurons is dependent on the level of DA in the hypothalamus. At low levels DA disinhibits orexin neurons whereas at high levels it facilitates GABA release, which may act as negative feedback to curb the excitatory orexinergic output to DA neurons. These mechanisms may have implications for consummatory and motivated behaviours.